Karakteristik Fisiko Kimia dan Organoleptik Bakso Daging Sapi, Bakso Daging Tikus, dan Bakso Daging Sapi Campur Daging Tikus dengan Penambahan Bahan Pengenyal dan Bumbu - Amalia, Lia; Bilqisthy , Salmiah Rahayu; Mardiah, Mardiah; Jumiono, Aji (Karimah Tauhid, 2024)
Meatballs have been known as the favorite food product among Indonesian people. Several factors affect consumer preferences in selecting meatballs, i.e., color, taste,e and texture, and texture, to determine the physical and chemical properties of beef meatballs, rat meatballs, and rat meatballs mixed beef meatballs. This study used a Complete Randomized Design of 1 factor with three levels of treatment and two replications for each treatment. The treatment consists of A1, 100% beef; A2, 100% rat meat; and A3, beef, 50% rat meat 50%. The analyzed data used Analysis of Variance (ANOVA) and followed Duncan's advanced test at a 95% confidence interval on organoleptic tests. The quality results of sensory tests on all three treatments of differences in meat composition had a natural effect on color and had no discernible impact on the meatball seaplane. The chemical properties of rat meatballs mixed with beef meatballs have a moisture content of 69.47%, ash content of 3.64%, protein content of 11.87%, fat content of 1.29%, and carbohydrate content of 8.49%. Tests of the supply of rat meatballs mixed with beef meatballs with Texture Profile Analysis included a hardness value of 1216.9 gf, springiness of 1,000 gs, cohesiveness of 0.621, gumminess of 754.2 and chewiness of 754.2. Average value Lightness (L*) 59.13 Redness (a*) 4.36 and Yellowness (b*) 14.49.